Antenatal depressive symptoms in rwanda: rates, risk factors, and social support - Marie Providence Umuziga; Darius Gishoma; Michaela Hynie; Laetitia Nyirazinyoye (BMC, 2022)
Abstract Background Prevalence of perinatal depression is high in Rwanda and has been found to be associated with the quality of relationship with partner. This study extends this work to examine the relationship between antenatal depressive symptoms and social support across several relationships among women attending antenatal care services. Methods Structured survey interviews were conducted with 396 women attending antenatal care services in 4 health centres in the Southern Province of Rwanda. The Edinburgh Postnatal Depression Scale (EPDS) and Maternity Social Support Scale (MSSS) were used to assess antenatal depressive symptoms and the level of support respectively. Socio-demographic and gestational information, pregnancy intentions, perceived general health status, and experience of violence were also collected. Univariate, bivariate analyses and a multivariate logistic regression model were performed to determine the relationship between social support and risk factors for antenatal depressive symptoms. Results More than half of respondents were married (55.1%) or living with a partner in a common-law relationship (28.5%). About a third (35.9%) were in their 6th month of pregnancy; the rest were in their third term. The prevalence of antenatal depressive symptoms was 26.6% (EPDS ≥ 12). Bivariate analyses suggested that partner and friend support negatively predict depression level symptoms. Adjusting for confounding variables such as unwanted pregnancy (AOR: 0.415, CI: 0.221- 0.778), parity (AOR: 0.336, CI: 0.113-1.000) and exposure to extremely stressful life events (AOR: 2.300, CI: 1.263- 4.189), partner support (AOR: 4.458, CI: 1.833- 10.842) was strongly significantly associated with antenatal depressive symptoms; women reporting good support were less likely to report depressive symptoms than those reporting poor support or those with no partner. Friend support was no longer significant. Conclusion The study revealed that social support may be a strong protector against antenatal depressive symptoms but only support from the partner. This suggests that strengthening support to pregnant women may be a successful strategy for reducing the incidence or severity of maternal mental health problems, but more work is required to assess whether support from the broader social network can compensate for absent or unsupportive partners.